Museum on first floor - Ghosh, Ayan (Jio Institute, 2023)
On the second level inside the BMC building, stained-glass windows illuminate a museum which traces the evolution and history of the Municipal Corporation and the stellar role of Frederick W. Stevens in the design of the building. This museum also has a collection of old maps of the Greater Mumbai Region and old photographs of Mumbai.